A deep-learning model for national scale modelling and mapping of sea level rise in Malaysia: the past, present, and future - Adebisi, N. (Taylor and Francis Ltd., 2021)
In this study, we conducted a holistic evaluation of current and future trend in coastal sea level at the 21 stations along Malaysiaâs coastline. For sea level prediction, univariate and 3 scenarios of multivariate Long Short Term Memory (LSTM) neural networks were trained with absolute sea level data and ocean-atmospheric variables. The result from the four scenario predictive models revealed that multivariate LSTM neural network trained with combined ocean-atmospheric variables performed best for modelling sea level variation, giving a mean RMSE and R accuracy of 0.060 and 0.861, respectively. The national sea level rise estimated from the average of sea level trend at all stations is 3.72 mm/yr for relative sea level and 3.68 mm/yr for absolute sea level. The 2050 and 2100 projections indicate that sea level will continue to rise but at a very slow rate with no acceleration. Â© 2021 Informa UK Limited, trading as Taylor & Francis Group.